EFEKTIVITAS PROGRAM SUMUT MAKMUR OLEH BADAN AMIL ZAKAT NASIONAL SUMATERA UTARA DALAM PEMBERDAYAAN EKONOMI UMAT DI KECAMATAN KOTA PINANG (Studi Kasus Bantuan Modal Bergulir Badan Amil Zakat Nasional Labuhanbatu Selatan) - Afifah Rahmadani; Andri Soemitra; Aqwa Naser Daulay (Studia Economica : Jurnal Ekonomi Islam, 2021)
The revolving capital assistance program is the provision of capital loans from the National Amil Zakat Agency of South Labuhanbatu in reducing capital loans that borrow funds from moneylenders, banks, and cooperatives. This study aims to determine and analyze (1) regarding the revolving capital assistance program at the National Amil Zakat Agency of South Labuhanbatu. (2) The role of the revolving capital assistance program of the South Labuhanbatu National Amil Zakat Agency in empowering the economy of the people in the District of Kota Pinang. (3) The effectiveness of the revolving capital assistance program of the South Labuhanbatu National Amil Zakat Agency in empowering the economy of the people in Kota Pinang District. The research approach carried out in this research is descriptive quantitative with data collection methods using observation, interviews and documentation. To analyze the data, the author uses a Likert scale and Miles and Huberman data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results of the study concluded that (1) the revolving capital assistance program in BAZNAS Labuhanbatu Selatan aims to empower the people's economy so that traders can fulfill their daily needs to be more empowered. (2) The role of the revolving capital assistance program is to increase independence in entrepreneurship, motivate recipients to strengthen ties of friendship among mosque congregations and to improve the family's economic standard of living. (3) The South Labuhanbatu BAZNAS revolving capital assistance program has been implemented effectively in empowering the economy of the people in Kota Pinang District with the average distribution scale value for the effectiveness of the revolving capital assistance program is 2.63